2019
DOI: 10.18028/rgfc.v8i2.5514
|View full text |Cite
|
Sign up to set email alerts
|

Relação Entre O Gerenciamento Tributário E a Evidenciação De Passivos Contingentes Tributários Em Empresas Listadas No Novo Mercado Da [B]3

Abstract: Esta pesquisa objetivou avaliar a relação entre o gerenciamento tributário e a evidenciação dos passivos contingentes tributários em empresas listadas no segmento do Novo Mercado da [B]3. O nível de divulgação do passivo contingente tributário por parte das empresas foi encontrado com base em um checklist elaborado de acordo com as exigências do CPC 25. Para medir o gerenciamento tributário, foram utilizadas as variáveis Effective Tax Rates (ETR), Cash Effective Tax Rates (CashETR) e Book-Tax Differences (BTD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The reflected evidence tends to recognize that BTD should be carefully analyzed in tax planning studies, as it seems more appropriate for studying results management, as pointed out by different studies, some very recent (Guenther et al, 2021;Magalhães & Ferreira, 2018;Martinez & Leal, 2019;Mohanadas et al, 2021). Therefore, this may be a theoretical explanation for the lack of statistical significance of the variable of interest in this research.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The reflected evidence tends to recognize that BTD should be carefully analyzed in tax planning studies, as it seems more appropriate for studying results management, as pointed out by different studies, some very recent (Guenther et al, 2021;Magalhães & Ferreira, 2018;Martinez & Leal, 2019;Mohanadas et al, 2021). Therefore, this may be a theoretical explanation for the lack of statistical significance of the variable of interest in this research.…”
Section: Discussionmentioning
confidence: 87%
“…The non-significance of BTD is based on the fact that this metric may no longer be one of the most appropriate for measuring tax aggressiveness, but is better applied to earnings management studies, as suggested by Guenther et al (2021), Magalhães and Ferreira (2018), and Martinez and Leal (2019). Therefore, further research on this metric is encouraged.…”
Section: Multiple Linear Regressionmentioning
confidence: 99%
“…As evidências refletidas caminham para o reconhecimento de que a BTD deve ser analisada com cuidado nos estudos de planejamento tributário, pois parece mais adequada para se estudar gerenciamento de resultado, como apontam diferentes estudos, alguns bem recentes (Guenther et al, 2021;Magalhães & Ferreira, 2018;Martinez & Leal, 2019;Mohanadas et al, 2021). Destarte, isso pode ser uma explicação teórica pela sua não significância estatística para com a variável de interesse desta pesquisa.…”
Section: Considerações Finaisunclassified
“…It would not allow them to distinguish the situation in the event of omission or when taxes on economic or financial operation did not apply, absent in the financial statements (Wallacer & Nacer, 1995). Thus, one cannot wait for an uncertain event to happen to assume obligations of recognition and disclosure of these past facts, because users would lose trust and would not be able to analyze the company's financial capacity (Magalhães & Ferreira, 2018).…”
Section: Tax Disclosurementioning
confidence: 99%